The Effect of Sustainability Reporting and Digital Transformation on Profitability with Green Finance as a Moderating Variable in Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2019–2023 - Suryaningsih, Yeny; Hidayati, Siti Aisyah; Suryani, Embun (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the effect of sustainability reporting and digital transformation on profitability, with green finance as a moderating variable. The population of this research consists of energy sector companies listed on the Indonesia Stock Exchange (IDX). Using a purposive sampling method, 10 companies were selected as the research sample. This study employs a causal-associative research design with a survey-based quantitative approach. Data were collected through documentation techniques by accessing secondary data in the form of annual reports and sustainability reports of energy companies during the 2019–2023 period, obtained from the official IDX website and each company’s website. The data were analyzed using Moderated Regression Analysis (MRA) with SPSS software. The results reveal that sustainability reporting has a significant positive effect on profitability, as measured by Return on Assets (ROA). Meanwhile, digital transformation shows a positive but insignificant effect on profitability. Furthermore, green finance is found to moderate the relationship between sustainability reporting and profitability but fails to moderate the relationship between digital transformation and profitability.